2022
DOI: 10.3390/su14031300
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Urban Food Action: Relevance of Food Pedagogies

Abstract: Cities strive to feed growing populations while at the same time minimize the environmental impacts of their food systems. To support cities to achieve their goals, they require systematic and practical actions, including identification of the needs and capacities of food practitioners to guide and support food-related policies and initiatives. This study aims to explore barriers to food-related actions in everyday settings and the potential of a food pedagogy framework to overcome such barriers. Semi-structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Prior studies identified the importance of each of the five themes of the framework in enabling individuals and communities to advance their health and well-being 22 and understand and take action to support sustainable food systems. 50 These themes comprise the food pedagogy framework that can achieve effective and sustainable food policies and urban-based food initiatives. With respect to urban food-based activities, the themes, such as 'Making use of (in)formal pedagogical spaces in communities' and 'Developing supportive and transparent systems', need to be reflected in government sectors and within policy making processes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies identified the importance of each of the five themes of the framework in enabling individuals and communities to advance their health and well-being 22 and understand and take action to support sustainable food systems. 50 These themes comprise the food pedagogy framework that can achieve effective and sustainable food policies and urban-based food initiatives. With respect to urban food-based activities, the themes, such as 'Making use of (in)formal pedagogical spaces in communities' and 'Developing supportive and transparent systems', need to be reflected in government sectors and within policy making processes.…”
Section: Discussionmentioning
confidence: 99%